EXTENDING THE KHALIL STAGE OF "KHESAB" DATES USING NEW METHOD OF PACKAGING AND MODIFIED CALCIUM FORMATION - Farag, Karim M.; Al-Masri, Hassan H. (Emirates Journal of Food and Agriculture, 1999)
The effect of calcium chloride alone or in a formulation containing glycerol on extendingthe khalal stage was studied utilizing wood shavings below and above treated strands during 1997 and 1998 seasons. After cold storage, khesab-treated fruits with CaCl2 plus glycerol significantly had lower percentage of rutab fruits when compared with the control or the wood shavings treatment. An added advantage on reducing rutab development was obtained when glycerol was combined with CaCl2 as compared with CaCl2 alone. The absence of wood shavings in the control resulted in significantly higher rutab development when compared with the wood shavings treatment during both seasons.Electrolyte leakage of khalal fruits, as indicated by electrical conductivity, of the wood shavingstreatment was significantly higher than that of CaCl2 alone or in the presence of glycerol in both seasons. Moreover, fruits embedded in wood shavings only had significantly lower electrolyte leakage than the control (without wood shavings) in both seasons at the khalal stage. This study provided evidence about the feasibility of using CaCl2 plus glycerol in the presence of wood shavings to extend the khalal stage of khesab dates and maintain their quality on a large scale